2009
DOI: 10.1007/s10544-008-9277-1
|View full text |Cite
|
Sign up to set email alerts
|

Sample preparation module for bacterial lysis and isolation of DNA from human urine

Abstract: Silica impregnated polymer monolithic columns may provide a simple method for lysing and extracting DNA from bacteria inside of microfluidic chips. Here we use Escherichia coli as a test organism for a point of care thermoplastic microfluidic module designed to take in a urine sample, mix it with lysis buffer, and perform a hybrid chemical/mechanical lysis and solid phase extraction of nucleic acids from the sample. To demonstrate proof-of-concept, we doped human hematuric urine samples with E. coli at concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 31 publications
1
44
0
3
Order By: Relevance
“…Polymer micro-solid phase extraction (μSPE) columns have been developed and utilized by numerous laboratories for the extraction and purification of DNA for POC sample preparation solutions. 8,9 In our own laboratory, we have even shown that DNA purification can be performed using these columns in low-resource settings by pressurizing extractions with a bicycle pump. 10 However, making the μSPE columns requires extensive polymer chemistry expertise to enable the precise control over porosity and flow-rates necessary to ensure nucleic acid capture.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer micro-solid phase extraction (μSPE) columns have been developed and utilized by numerous laboratories for the extraction and purification of DNA for POC sample preparation solutions. 8,9 In our own laboratory, we have even shown that DNA purification can be performed using these columns in low-resource settings by pressurizing extractions with a bicycle pump. 10 However, making the μSPE columns requires extensive polymer chemistry expertise to enable the precise control over porosity and flow-rates necessary to ensure nucleic acid capture.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that the extraction efficiency of the membrane-based precipitation used in the device may have actually been better than the silica-based commercial kit used to prepare our qPCR swab samples. Membrane-based precipitation has been shown to be effective at even low concentrations of DNA, while previous reports have shown significant genomic DNA losses from silica-based kits at DNA concentrations below 10 4 CFU/mL (Kulinski et al 2009). We saw a reduced bacterial load in our qPCR measurements when comparing our urethral swab NG bacterial load quantifications to a previous study (Priest et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…On-chip end-point fluorescence detection was carried out by means of an external LED excitation source and a spectrophotometer. Theoretical detection limits were in the order of 1 molecule in 50 L. Previous versions of this device containing the same monolithic SPE column, but no on-chip PCR, were also used to isolate nucleic acids from gram positive and negative bacteria [93,94] and viruses [95] in whole blood [94], urine [93] and cell culture [95] samples.…”
Section: Sample Purification Preconcentration and Extractionmentioning
confidence: 99%